2004
DOI: 10.1111/j.1365-277x.2004.00552.x
|View full text |Cite
|
Sign up to set email alerts
|

The health benefits of omega‐3 polyunsaturated fatty acids: a review of the evidence

Abstract: The UK dietary guidelines for cardiovascular disease acknowledge the importance of long-chain omega-3 polyunsaturated fatty acids (PUFA) - a component of fish oils - in reducing heart disease risk. At the time, it was recommended that the average n-3 PUFA intake should be increased from 0.1 to 0.2 g day(-1). However, since the publication of these guidelines, a plethora of evidence relating to the beneficial effects of n-3 PUFAs, in areas other than heart disease, has emerged. The majority of intervention stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
453
2
35

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 733 publications
(493 citation statements)
references
References 73 publications
3
453
2
35
Order By: Relevance
“…Among various classes of fatty acids, omega‐3 polyunsaturated fatty acids (PUFA) are known to have various health benefits, such as prevention of CVD and rheumatoid arthritis, as well as improvements to brain function and mental stability (Ruxton, Reed, Simpson, & Millington, 2004). While omega‐3 has traditionally been considered beneficial only when maintained in a suitable ratio with omega‐6, some research has subsequently challenged this theory, suggesting that the benefit of omega‐3 should be considered solely in terms of total intake (Stanley et al., 2007).…”
Section: Effects Of Farming Systems On Meat Qualitymentioning
confidence: 99%
“…Among various classes of fatty acids, omega‐3 polyunsaturated fatty acids (PUFA) are known to have various health benefits, such as prevention of CVD and rheumatoid arthritis, as well as improvements to brain function and mental stability (Ruxton, Reed, Simpson, & Millington, 2004). While omega‐3 has traditionally been considered beneficial only when maintained in a suitable ratio with omega‐6, some research has subsequently challenged this theory, suggesting that the benefit of omega‐3 should be considered solely in terms of total intake (Stanley et al., 2007).…”
Section: Effects Of Farming Systems On Meat Qualitymentioning
confidence: 99%
“…Epidemiological studies indicated that, among PUFAn-3, α-linolenic acid (18:3n-3; ALA) is associated with reduced risk of cardiovascular diseases, and the LC-PUFAn-3, notably docosapentaenoic acid (22:6n-3; DHA), are recognized for their beneficial effects on heart health, proper prenatal brain and eye development and maintenance of neural and visual tissues throughout life (Ruxton et al, 2004). Metabolically, ALA is the precursor of eicosapentaenoic (20:5n-3; EPA), docosapentaenoic (22:5n-3; DPA) and DHA.…”
Section: Introductionmentioning
confidence: 99%
“…Particular attention has been paid to the dietary long-chain n-3 polyunsaturated fatty acid (n-3 PUFA), such as eicosapentaenoic (EPA, and docosahexaenoic (DHA,. These fatty acids are known to be crucial for normal growth and development (reviewed by Ruxton et al, 2004). They also reduce risk of cardio-vascular disease (reviewed by Givens and Gibbs, 2008), decrease incidence of age-related eye disease (SanGiovanni et al, 2008), positively alter human red blood cell fatty-acid composition (Barcelo-Coblijn et al, 2008), decrease risk of cancer and have a number of other health benefits (Berquin et al, 2008;Li et al, 2008;Mozaffarian, 2008).…”
Section: Introductionmentioning
confidence: 99%